اختيار طب الأسنان كمهنة في الجامعة الدولية الخاصة للعلوم والتكنولوجيا - صايمة, رويدة (Latakia University Journal -Medical Sciences Series, 2019)
The motivations for choosing a career are yet not clearly defined. Aims: The purpose of this study was to investigate why students at IUST dental faculty had chosen dentistry as their career. Methods & Materials: A sample of 785 students was conducted. Questionnaires were handed to students comprised of 20 options. 27 % of participants were females. The data were encoded and analyzed using the SPSS software package. Chi-square was used to determine the relationship between the variables. Results: Both males and females like to work with their hands 13%. Although 12% chose Q5 and Q1 which indicate that they want to be self-employed or one of their relatives or friends are dentists, 5% chose dentistry because their GPA. The results presented are the first reported data for a sample of students in Syria. In total we noticed that 36% of the whole participants chose dentistry for economic status, and 18% because one of their relatives is a dentist or family dentist who encourages them and this proves that dentists in Syria are satisfied with their profession. Conclusion: It is recommended that the survey is repeated for students in public university and comparing the results obtained with the results reported here. Understanding students reasons may aid concerned authorities to provide them with a full and accurate picture of the profession. خلفية وهدف البحث: إن دراسة سبب اختيار مهنة ما لم تَعرف بشكل واضح, لذلك تهدف هذه الدراسة الى التحري عن سبب اختيار طلاب الجامعة لطب الأسنان كمهنة. المواد والطرق : بلغ عدد المشاركين في البحث 785 طالباً وطالبة, وزعت عليهم بشكلِ شخصي استبيانات تحوي عشرين احتمالاً. تم تحليل وترميز النتائج باستخدام برنامج الحزم الإحصائية للعلوم المجتمعية, ثم تطبيق تحليل كاي مربع لتحديد العلاقة بين المتغيرات. النتائج : كل من الذكور والإناث يرغب بالعمل اليدوي بنسبة 13%, و12% اختاروا مهنة طب الأسنان لأن أحد أقربائهم أو أصدقاءهم طبيب أسنان. 5% اختاروا لأن معدلهم يؤهلهم لدخول الكلية . 36% من عدد المشاركين اختاروا المهنة لأسباب اقتصادية, و18% لأن عائلتهم أو أصدقاءهم أو طبيب أسنانهم شجعوهم على اختيار طب الاسنان. وهذا يشير إلى رضا أطباء الأسنان من مهنتهم. الاستنتاج: هذه النتائج هي الاولى لعينة من الطلبة السوريين . ننصح بإجراء هذا المسح في الجامعات الحكومية ومقارنتها بدراستنا. ان فهم اسباب اختيار الطلاب لدراسة طب الأسنان يساعد السلطات المعنية على تأمين صورة واضحة وكاملة لمهنة طب الاسنان.